2009
DOI: 10.1111/j.1399-3038.2009.00853.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparability of a hand‐held nitric oxide analyser with online and offline chemiluminescence‐based nitric oxide measurement

Abstract: Practicability is crucial for successful implementation of fractional exhaled nitric oxide (FeNO) measurement into asthma management. The study aimed at comparing a conventional chemiluminescence NO analyser (EcoMedics) with a hand-held device (NIOX MINO) and offline FeNO measurement using a commercially available system in an unselected cohort of children aged 6-16 yr. A secondary objective was to confirm FeNO stability over time in 15 samples from adult volunteers obtained using the offline system. Sixty-six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 35 publications
(52 reference statements)
5
30
0
1
Order By: Relevance
“…The measurement of FeNO has been standardised for clinical use in a joint guideline from the ATS and ERS [98]. The conventional chemiluminescence FeNO analyser, the hand-held device and offline FeNO measurements have been shown to produce similar results in children older than 5 years of age with a success rate of >70% and with an overall coefficient of repeatability of around 1.6-3.2 ppb [99][100][101][102][103][104]. A low FeNO (<20 ppb) in children with asthma not treated with ICSs indicates that eosinophilic inflammation and responsiveness to corticosteroids are less likely.…”
Section: Exhaled Nitric Oxide Fractionmentioning
confidence: 99%
“…The measurement of FeNO has been standardised for clinical use in a joint guideline from the ATS and ERS [98]. The conventional chemiluminescence FeNO analyser, the hand-held device and offline FeNO measurements have been shown to produce similar results in children older than 5 years of age with a success rate of >70% and with an overall coefficient of repeatability of around 1.6-3.2 ppb [99][100][101][102][103][104]. A low FeNO (<20 ppb) in children with asthma not treated with ICSs indicates that eosinophilic inflammation and responsiveness to corticosteroids are less likely.…”
Section: Exhaled Nitric Oxide Fractionmentioning
confidence: 99%
“…One study 63 noted that the direction of disagreement was different in children aged over and under 12 years. l The back-transformed Bland-Altman statistics 63 and range of ratios reported 62 indicate a wide range of agreement and suggest that the devices are not interchangeable.…”
Section: In Childrenmentioning
confidence: 99%
“…Six studies [reported across nine studies and one sponsor's submission (Fukuhara 2013)] were carried out in adults, [50][51][52][53][54][55][56][57]64 three were carried out in an unspecified age group [58][59][60] (two of which had potentially largely overlapping cohorts and will be considered as one study) 58,59 and three were carried out in children. [61][62][63] All studies included at least some asthmatic patients, except that by de Laurentiis et al 57 Mean FeNO values varied across the studies (from 7 ppb in a healthy cohort of patients 52,53 to 64.3 ppb in an asthmatic cohort 54 ). Devices studied in adults/unspecified age groups were the EndoNO (SERES, Aix en Provence, France), N-6008 (SIR, Madrid, Spain), NA623N (CHEST Inc., Tokyo, Japan), NOA 280i (Sievers, Boulder, CO, USA), CLD 88sp (ECO MEDICS, Dürnten, Switzerland), NOA (Sievers, Boulder, CO, USA) and LR2000 (Logan Research Ltd, Rochester, UK), whereas devices tested in children were the CLD 88 and CLD 77 (ECO MEDICS).…”
Section: Niox Mino Compared With Other Chemiluminescent Devices In Admentioning
confidence: 99%
“…To date, NIOX MINO Ò has been compared with three chemiluminescence NO analyzers, the NIOX Ò , Ecomedics and Sievers NOA280i [18][19][20][21][22][23][24][25][26][27][28][29][30]. All these studies showed agreement between the FeNO values obtained with the devices being studied, with a clinically acceptable level of agreement shown with NIOX [19-22, 25, 26] and Ecomedics [29].…”
Section: Discussionmentioning
confidence: 96%